Mercy, Mental Illness, and the Moral Significance of Christian History The Story of Fr. Juan Gilabert-Jofre, O. de. M. - Romero, Miguel J. (2018)
This essay is concerned with the way theologians account for the moral significance of extraordinary and exceptional moments in the history of Christian faith and practice. A particular interest is how contemporary models and presumptions about the exceptionality of impairment and illness (i.e., disability, broadly construed) can distort the understanding of the theological and practical responses to impairment and illness that are found in Christian history. That methodological question is explored through the story of Fr. Juan Gilabert-Jofre, O. de. M., and the history of the first psychiatric hospital founded in Europe, at the beginning of the 15th century-Hospital D'Innocents, Folls e Orats. When it comes to extraordinary and exceptional events in Christian history, it is a mistake to presume that the principle actors were "extraordinary" and "exceptional" persons. The problem is most acute when we transpose the memory of exemplary Christian responses to impairment, illness, and injury into lofty stories of virtually unattainable moral heroics. Through a reading of Jofre's moral formation as a Mercedarian priest, theologians are reminded that the moral witness of Christian exemplars always begins in the crucible of ordinary faith, shaped and oriented through mundane and unexceptional formation into the seemingly insignificant rhythms of moral goodness.
Keywords: Christian Theology; Juan Gilabert-Jofre; Mercedarian; Disability; Ethics; History; Mental Illness; Mercy; Moral Formation